Potential effect of Olea europea leaves, Sonchus oleraceus leaves and Mangifera indica peel extracts on aromatase activity in human placental microsomes and CYP19A1 expression in MCF-7 cell line: Comparative study - Shaban, N Z; Hegazy, W A; Abdel-Rahman, S M; Awed, O M; Khalil, S A (Cellular and Molecular Biology, 2016)
Aromatase inhibitors (AIs) provide novel approaches to the adjuvant therapy for postmenopausal women with estrogen-receptor-positive (ER+) breast cancers. In this study, different plant extracts from Olea europaea leaves (OLE), Sonchus oleraceus L. (SOE) and Mangifera indica peels (MPE) were prepared to identify phytoconstituents and measure antioxidant capacities. The effects of these three extracts on aromatase activity in human placental microsomes were evaluated. Additionally, the effects of these extracts on tissue-specific promoter expression of CYP19A1 gene in cell culture model (MCF-7) were assessed using qRT-PCR. Results showed a concentration-dependent decrease in aromatase activity after treatment with OLE and MPE, whereas, SOE showed a biphasic effect. The differential effects of OLE, SOE and MPE on aromatase expression showed that OLE seems to be the most potent suppressor followed by SOE and then MPE. These findings indicate that OLE has effective inhibitory action on aromatase at both the enzymatic and expression levels, in addition to its cytotoxic effect against MCF-7 cells. Also, MPE may be has the potential to be used as a tissue-specific aromatase inhibitor (selective aromatase inhibitor) and it may be promising to develop a new therapeutic agent against ER+ breast cancer.